Cyclic AMP Accumulation in Migraine Induction - Ana B Chelse; Leon G Epstein (Pediatric Neurology Briefs, 2015)
Investigators from Danish Headache Centre, Glostrup Hospital, and the University of Copenhagen investigated whether intracellular cyclic AMP accumulation induced migraine attacks among 14 migraine patients without aura.